Pengaruh Pembelajaran Daring terhadap Pemahaman Materi Mahasiswa - Palma Juanta; Sola Gratia Hutasoit; Yusup Aritonang; Tan Lisaifung (INDO PUBLISHING, 2026)
This study aims to analyze the effect of online learning on students' material comprehension at Universitas Prima Indonesia. A quantitative approach with a survey design was employed, involving 60 respondents selected through random sampling. Data were collected using a Likert-scale questionnaire (15 items) and analyzed using descriptive statistics and the Spearman's Rank correlation test due to non-normal data distribution (Sig. < 0.05). The results showed that both online learning implementation (mean=17.30) and students' comprehension (mean=11.91) were in the